Sabkha Ecosystems Volume II: West and Central Asia - Khan, M. Ajmal; Böer, Benno; Kust, German S.; Barth, Hans-Jörg (Tasks for Vegetation Science, 2006)
Sabkha Ecosystems Volume I: The Arabian Peninsula and Adjacent Countries was published in 2002. It was the first comprehensive volume dealing with the subject of sabkha research, and sabkha environmental management. Valuable new information was provided for the sabkha of numerous countries on and adjacent to the Arabian Peninsula. This new volume now follows up on this important process, and provides data and information on salt desert ecosystems of numerous West and Central Asian countries, including many of which are located in the Arabian Peninsula. The information provided assists the reader to better understand sabkha geology, hydrology, geomorphology, zoology, botany, ecology, ecosystem functioning, as well as sabkha conservation, utilisation, and development. The volume is paramount literature for anyone dealing with sabkha research and development.